Establishment and Marketing of New Oil Benchmarks in the Structure of Global Oil and Oil Products Mercantile Trade: the Russian Case - Guliyev, Igbal A.; Litvinyuk, Igor I.; Mekhdiev, Elnur T.; Bondarenko, Victor N.; Vereshchagin, Alexandr S. (International Journal of Energy Economics and Policy, 2018)
The organization of oil and oil products stock trading that requires for independent national price indicators establishment, will promote the formation of a fair prices for energy commodities, the extension of influence of the national currency on the global market and the decrease of impact of external fluctuations of global economy. In this article, the authors review the possibility of inclusion of new oil benchmarks in the structure of the global oil and oil products mercantile trade. In particular, the Russian case is the major research subject, and the assessment is made for the purpose of strengthening the country’s leverage over free market prices and in the interests of the state budget and national companies. Special attention is also given to the analysis of the contemporary contract structure of the global oil market and imposed risks. The authors develop the methodological framework for oil and oil products price indicators calculation and the suggestions about the promotion and marketing of Russian oil benchmark on the international level. Keywords: oil, oil products, mercantile exchange, benchmark, global oil market, international relations JEL Classifications: F13, N70, O24, Q41